RANDOMIZED CONTROL TRIAL COMPLEMENTARY THERAPY GARLIC CAPSULES IN HYPERTENSION PATIENTS - Ana Amalia; Fendri Luukmanto (Universitas Muhammadiyah Kalimantan Timur, 2021)
Hypertension is a type of disease that is difficult to control, this is because in some cases there are no signs and symptoms that appear. The provision of pharmacological therapy is deemed insufficient to control the patient's blood pressure, so it is necessary to conduct research related to complementary therapies. Complementary therapy that can be given can be in the form of garlic capsules which contain allicin which is efficacious in lowering blood pressure. The purpose of this study was to determine the effect of complementary therapy with garlic capsules (Allium Sativum Linn) on the value of Mean Arterial Pressure (MAP) in patients with uncontrolled hypertension. The study design was a Randomized Controlled Trial (RCT). Measurement of MAP was carried out pre-post therapy, namely at week 0, 1, 2, 3, and 4. The sampling technique used simple random sampling, the sample was divided into a control group (placebo) and a treatment group each consisting of 30 people. The results of sociodemographic characteristics show that more people with hypertension are at the age of 45-54 years, female gender, last education is high school, work as a farmer, long suffering from hypertension <5 years. Paired t-test analysis showed that the average result of the decrease in MAP in the garlic capsule group was 20.23 with a P Value of 0.000, which means that there is a significant difference between the MAP value before and after administration of garlic capsules. The placebo group had a P Value of 0.258, this shows that there is no difference in MAP before and after giving placebo. The conclusion of this study is that giving garlic capsules can reduce blood pressure in hypertensive patients.